COMPARISON OF LOSARTAN AND LISINOPRIL EFFECTIVENESS FOR GLOMERULAR AND TUBULAR MARKERS OF RENAL DYSFUNCTION IN CHRONIC HEART FAILURE - U. K. Kamilova; Z. D. Rasulova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To compare the losartan and lisinopril influence on glomerular and tubular markers rates of renal dysfunction in I-III functional class (FC) chronic heart failure (CHF). Material and methods. Totally 92 patients studied with I-III FC CHF. First group (I) consisted of 47 patients taking losartan as addition to standard treatment for 6 months; second group (II) — 45 patients took lisinopril. All patients underwent glomerular filtration rate estimation (MDRD GFR) and enzymes levels in urine: alanine transaminase (ALT), aspartat transaminase (AST), alkaline phosphanase (AP). Results. The results showed that GFR <60 ml/min in I and II groups was found in 18 (38,3%) and 17 (37,8%) patients, resp. Baseline data analysis of urine enzymes that characterize functional condition of renal tubules, showed that in GFR <60 ml/min patients there is significant (p<0,05) increase of ALT, AST, AP in urine: for I group patients by 45,2%, 31,8%, 78,2%, resp., and for II group — 43,6%, 33,5%, 73,9%, resp., comparing to the patients with GFR >60 ml/min. Six month treatment with inclusion of losartan and lisinopril led to decrease of enzymes levels in urine to increase of GFR comparing to baseline. Conclusion. GFR and the level of fermenturia are the early predictors of tubular epitelium in kidneys, and can be treated as early predictors of renal dysfunction in CHF. Six month treatment with losartan and lisinopril increases GFR and significantly decreases fermenturia, hence improving the condition of tubular epithelium and showin nephroprotective effect.